Safety of Surgery in benign Prostatic Hyperplasia Patients on Antiplatelet or Anticoagulant Therapy: A Systematic Review and Meta-Analysis - Liang, Xiongfa; Wu, Weizhou; Huang, Yapeng; Zhang, Shike; Huang, Jian; Zeng, Tao; Zhong , Fangling; Yong, Laichang; Duan, Xiaolu; Chao, Cai; et al. (Urology Journal, 2020)
Purpose: The management strategies of anticoagulant (AC) or antiplatelet (AP) therapy in the preoperative period of benign prostatic hyperplasia (BPH) is still controversial. Therefore, a meta-analysis to systematically evaluate the surgical safety for BPH patients on AC or AP therapy was performed. Materials and Methods: The protocol for the review is available on PROSPERO (CRD42018105800). A literature search was performed by using MEDLINE, Web of Science, PubMed, Cochrane library, and Embase. Summarized odds ratios (OR), mean difference (MD) and 95% confidence intervals (CI) were used to assess the difference in outcomes. Results: We identified 13 trials with a total of 3767 patients. An intragroup significant difference was found in bleeding complications and blood transfusions when undergoing transurethral resection of the prostate (TURP). For laser surgery, the intragroup significant difference was found in the result of blood transfusion. Bridging therapy would not cause a higher risk of bleeding complications and blood transfusion during the perioperative period. Besides, no difference existed in operation time, catheterization time, hospitalization, and thromboembolic events. Conclusion: Patients with BPH on perioperative AC/AP therapy would have a risk of postoperative hemorrhage after TURP or laser treatments. To reduce the risk of hemorrhage, bridging therapy could be a good choice.